Electrostatic model of dielectric elastomer generator based on finite element - Jianbo Cao (Nature Portfolio, 2021)
Abstract When dielectric elastomer materials are used for power generation, bias voltage is applied at both ends of dielectric elastomer film, and there are equal amounts of heterogeneous charges on both sides of the film, so Maxwell electrostatic force is always coupled in the process of power generation. In order to investigate the distribution of Maxwell stress in dielectric elastomer material under electric field, the electrostatic model of dielectric elastomer generator is established in COMSOL finite element simulation software environment in this paper. The distribution of electrostatic force is studied from two aspects of theoretical derivation and simulation, and the magnitude and direction of electrostatic force are determined. The simulation results show that the Maxwell electrostatic force can be equivalent to the tensile force along the film plane and the extrusion force perpendicular to the plane, and they are the same.